Predictors of concurrent heroin use among patients on opioid maintenance treatment in France: a multilevel study over 11 years - Eric Janssen; Mike Vuolo; Stanislas Spilka; Guillaume Airagnes (BMC, 2024)
Abstract Background Consistent reports from health professionals suggest that heroin is commonly used by patients undergoing opioid maintenance treatment (OMT) in France, potentially jeopardizing their recovery process. However, there has been no formal epidemiological assessment on the matter. Methods We use a yearly updated compendium retrieving information on patients admitted in treatment centres in France between 2010 and 2020. Given the hierarchical nature of the data collection, we conduct 2-level modified Poisson regressions to estimate the risks of past month heroin use among patients on OMT. Results Despite an overall decreasing trend over time, heroin use among patients on OMT is indeed common, with half of patients declaring concurrent use. Our study unveils differentiated risks of heroin use vary according to the type of OMT, with patients on methadone more likely to use heroin compared to those on buprenorphine. The use of multilevel-related measures also uncovers high heterogeneity among patients' profiles, reflecting different stages in the treatment process, as well as differentiated practices across treatment centres. Conclusion Opioid maintenance treatment is associated with heroin use, in particular when methadone is involved. The heterogeneity among patients on OMT should be given particular attention, as it underscores the need for tailored interventions.